Linear Algebra Examples

Find the Eigenvalues [[1,3,2,11],[0,-1,3,8],[0,0,-2,4],[0,0,0,2]]
[132110-13800-240002]⎢ ⎢ ⎢ ⎢13211013800240002⎥ ⎥ ⎥ ⎥
Step 1
Set up the formula to find the characteristic equation p(λ).
p(λ)=determinant(A-λI4)
Step 2
The identity matrix or unit matrix of size 4 is the 4×4 square matrix with ones on the main diagonal and zeros elsewhere.
[1000010000100001]
Step 3
Substitute the known values into p(λ)=determinant(A-λI4).
Tap for more steps...
Step 3.1
Substitute [132110-13800-240002] for A.
p(λ)=determinant([132110-13800-240002]-λI4)
Step 3.2
Substitute [1000010000100001] for I4.
p(λ)=determinant([132110-13800-240002]-λ[1000010000100001])
p(λ)=determinant([132110-13800-240002]-λ[1000010000100001])
Step 4
Simplify.
Tap for more steps...
Step 4.1
Simplify each term.
Tap for more steps...
Step 4.1.1
Multiply -λ by each element of the matrix.
p(λ)=determinant([132110-13800-240002]+[-λ1-λ0-λ0-λ0-λ0-λ1-λ0-λ0-λ0-λ0-λ1-λ0-λ0-λ0-λ0-λ1])
Step 4.1.2
Simplify each element in the matrix.
Tap for more steps...
Step 4.1.2.1
Multiply -1 by 1.
p(λ)=determinant([132110-13800-240002]+[-λ-λ0-λ0-λ0-λ0-λ1-λ0-λ0-λ0-λ0-λ1-λ0-λ0-λ0-λ0-λ1])
Step 4.1.2.2
Multiply -λ0.
Tap for more steps...
Step 4.1.2.2.1
Multiply 0 by -1.
p(λ)=determinant([132110-13800-240002]+[-λ0λ-λ0-λ0-λ0-λ1-λ0-λ0-λ0-λ0-λ1-λ0-λ0-λ0-λ0-λ1])
Step 4.1.2.2.2
Multiply 0 by λ.
p(λ)=determinant([132110-13800-240002]+[-λ0-λ0-λ0-λ0-λ1-λ0-λ0-λ0-λ0-λ1-λ0-λ0-λ0-λ0-λ1])
p(λ)=determinant([132110-13800-240002]+[-λ0-λ0-λ0-λ0-λ1-λ0-λ0-λ0-λ0-λ1-λ0-λ0-λ0-λ0-λ1])
Step 4.1.2.3
Multiply -λ0.
Tap for more steps...
Step 4.1.2.3.1
Multiply 0 by -1.
p(λ)=determinant([132110-13800-240002]+[-λ00λ-λ0-λ0-λ1-λ0-λ0-λ0-λ0-λ1-λ0-λ0-λ0-λ0-λ1])
Step 4.1.2.3.2
Multiply 0 by λ.
p(λ)=determinant([132110-13800-240002]+[-λ00-λ0-λ0-λ1-λ0-λ0-λ0-λ0-λ1-λ0-λ0-λ0-λ0-λ1])
p(λ)=determinant([132110-13800-240002]+[-λ00-λ0-λ0-λ1-λ0-λ0-λ0-λ0-λ1-λ0-λ0-λ0-λ0-λ1])
Step 4.1.2.4
Multiply -λ0.
Tap for more steps...
Step 4.1.2.4.1
Multiply 0 by -1.
p(λ)=determinant([132110-13800-240002]+[-λ000λ-λ0-λ1-λ0-λ0-λ0-λ0-λ1-λ0-λ0-λ0-λ0-λ1])
Step 4.1.2.4.2
Multiply 0 by λ.
p(λ)=determinant([132110-13800-240002]+[-λ000-λ0-λ1-λ0-λ0-λ0-λ0-λ1-λ0-λ0-λ0-λ0-λ1])
p(λ)=determinant([132110-13800-240002]+[-λ000-λ0-λ1-λ0-λ0-λ0-λ0-λ1-λ0-λ0-λ0-λ0-λ1])
Step 4.1.2.5
Multiply -λ0.
Tap for more steps...
Step 4.1.2.5.1
Multiply 0 by -1.
p(λ)=determinant([132110-13800-240002]+[-λ0000λ-λ1-λ0-λ0-λ0-λ0-λ1-λ0-λ0-λ0-λ0-λ1])
Step 4.1.2.5.2
Multiply 0 by λ.
p(λ)=determinant([132110-13800-240002]+[-λ0000-λ1-λ0-λ0-λ0-λ0-λ1-λ0-λ0-λ0-λ0-λ1])
p(λ)=determinant([132110-13800-240002]+[-λ0000-λ1-λ0-λ0-λ0-λ0-λ1-λ0-λ0-λ0-λ0-λ1])
Step 4.1.2.6
Multiply -1 by 1.
p(λ)=determinant([132110-13800-240002]+[-λ0000-λ-λ0-λ0-λ0-λ0-λ1-λ0-λ0-λ0-λ0-λ1])
Step 4.1.2.7
Multiply -λ0.
Tap for more steps...
Step 4.1.2.7.1
Multiply 0 by -1.
p(λ)=determinant([132110-13800-240002]+[-λ0000-λ0λ-λ0-λ0-λ0-λ1-λ0-λ0-λ0-λ0-λ1])
Step 4.1.2.7.2
Multiply 0 by λ.
p(λ)=determinant([132110-13800-240002]+[-λ0000-λ0-λ0-λ0-λ0-λ1-λ0-λ0-λ0-λ0-λ1])
p(λ)=determinant([132110-13800-240002]+[-λ0000-λ0-λ0-λ0-λ0-λ1-λ0-λ0-λ0-λ0-λ1])
Step 4.1.2.8
Multiply -λ0.
Tap for more steps...
Step 4.1.2.8.1
Multiply 0 by -1.
p(λ)=determinant([132110-13800-240002]+[-λ0000-λ00λ-λ0-λ0-λ1-λ0-λ0-λ0-λ0-λ1])
Step 4.1.2.8.2
Multiply 0 by λ.
p(λ)=determinant([132110-13800-240002]+[-λ0000-λ00-λ0-λ0-λ1-λ0-λ0-λ0-λ0-λ1])
p(λ)=determinant([132110-13800-240002]+[-λ0000-λ00-λ0-λ0-λ1-λ0-λ0-λ0-λ0-λ1])
Step 4.1.2.9
Multiply -λ0.
Tap for more steps...
Step 4.1.2.9.1
Multiply 0 by -1.
p(λ)=determinant([132110-13800-240002]+[-λ0000-λ000λ-λ0-λ1-λ0-λ0-λ0-λ0-λ1])
Step 4.1.2.9.2
Multiply 0 by λ.
p(λ)=determinant([132110-13800-240002]+[-λ0000-λ000-λ0-λ1-λ0-λ0-λ0-λ0-λ1])
p(λ)=determinant([132110-13800-240002]+[-λ0000-λ000-λ0-λ1-λ0-λ0-λ0-λ0-λ1])
Step 4.1.2.10
Multiply -λ0.
Tap for more steps...
Step 4.1.2.10.1
Multiply 0 by -1.
p(λ)=determinant([132110-13800-240002]+[-λ0000-λ0000λ-λ1-λ0-λ0-λ0-λ0-λ1])
Step 4.1.2.10.2
Multiply 0 by λ.
p(λ)=determinant([132110-13800-240002]+[-λ0000-λ0000-λ1-λ0-λ0-λ0-λ0-λ1])
p(λ)=determinant([132110-13800-240002]+[-λ0000-λ0000-λ1-λ0-λ0-λ0-λ0-λ1])
Step 4.1.2.11
Multiply -1 by 1.
p(λ)=determinant([132110-13800-240002]+[-λ0000-λ0000-λ-λ0-λ0-λ0-λ0-λ1])
Step 4.1.2.12
Multiply -λ0.
Tap for more steps...
Step 4.1.2.12.1
Multiply 0 by -1.
p(λ)=determinant([132110-13800-240002]+[-λ0000-λ0000-λ0λ-λ0-λ0-λ0-λ1])
Step 4.1.2.12.2
Multiply 0 by λ.
p(λ)=determinant([132110-13800-240002]+[-λ0000-λ0000-λ0-λ0-λ0-λ0-λ1])
p(λ)=determinant([132110-13800-240002]+[-λ0000-λ0000-λ0-λ0-λ0-λ0-λ1])
Step 4.1.2.13
Multiply -λ0.
Tap for more steps...
Step 4.1.2.13.1
Multiply 0 by -1.
p(λ)=determinant([132110-13800-240002]+[-λ0000-λ0000-λ00λ-λ0-λ0-λ1])
Step 4.1.2.13.2
Multiply 0 by λ.
p(λ)=determinant([132110-13800-240002]+[-λ0000-λ0000-λ00-λ0-λ0-λ1])
p(λ)=determinant([132110-13800-240002]+[-λ0000-λ0000-λ00-λ0-λ0-λ1])
Step 4.1.2.14
Multiply -λ0.
Tap for more steps...
Step 4.1.2.14.1
Multiply 0 by -1.
p(λ)=determinant([132110-13800-240002]+[-λ0000-λ0000-λ000λ-λ0-λ1])
Step 4.1.2.14.2
Multiply 0 by λ.
p(λ)=determinant([132110-13800-240002]+[-λ0000-λ0000-λ000-λ0-λ1])
p(λ)=determinant([132110-13800-240002]+[-λ0000-λ0000-λ000-λ0-λ1])
Step 4.1.2.15
Multiply -λ0.
Tap for more steps...
Step 4.1.2.15.1
Multiply 0 by -1.
p(λ)=determinant([132110-13800-240002]+[-λ0000-λ0000-λ0000λ-λ1])
Step 4.1.2.15.2
Multiply 0 by λ.
p(λ)=determinant([132110-13800-240002]+[-λ0000-λ0000-λ0000-λ1])
p(λ)=determinant([132110-13800-240002]+[-λ0000-λ0000-λ0000-λ1])
Step 4.1.2.16
Multiply -1 by 1.
p(λ)=determinant([132110-13800-240002]+[-λ0000-λ0000-λ0000-λ])
p(λ)=determinant([132110-13800-240002]+[-λ0000-λ0000-λ0000-λ])
p(λ)=determinant([132110-13800-240002]+[-λ0000-λ0000-λ0000-λ])
Step 4.2
Add the corresponding elements.
p(λ)=determinant[1-λ3+02+011+00+0-1-λ3+08+00+00+0-2-λ4+00+00+00+02-λ]
Step 4.3
Simplify each element.
Tap for more steps...
Step 4.3.1
Add 3 and 0.
p(λ)=determinant[1-λ32+011+00+0-1-λ3+08+00+00+0-2-λ4+00+00+00+02-λ]
Step 4.3.2
Add 2 and 0.
p(λ)=determinant[1-λ3211+00+0-1-λ3+08+00+00+0-2-λ4+00+00+00+02-λ]
Step 4.3.3
Add 11 and 0.
p(λ)=determinant[1-λ32110+0-1-λ3+08+00+00+0-2-λ4+00+00+00+02-λ]
Step 4.3.4
Add 0 and 0.
p(λ)=determinant[1-λ32110-1-λ3+08+00+00+0-2-λ4+00+00+00+02-λ]
Step 4.3.5
Add 3 and 0.
p(λ)=determinant[1-λ32110-1-λ38+00+00+0-2-λ4+00+00+00+02-λ]
Step 4.3.6
Add 8 and 0.
p(λ)=determinant[1-λ32110-1-λ380+00+0-2-λ4+00+00+00+02-λ]
Step 4.3.7
Add 0 and 0.
p(λ)=determinant[1-λ32110-1-λ3800+0-2-λ4+00+00+00+02-λ]
Step 4.3.8
Add 0 and 0.
p(λ)=determinant[1-λ32110-1-λ3800-2-λ4+00+00+00+02-λ]
Step 4.3.9
Add 4 and 0.
p(λ)=determinant[1-λ32110-1-λ3800-2-λ40+00+00+02-λ]
Step 4.3.10
Add 0 and 0.
p(λ)=determinant[1-λ32110-1-λ3800-2-λ400+00+02-λ]
Step 4.3.11
Add 0 and 0.
p(λ)=determinant[1-λ32110-1-λ3800-2-λ4000+02-λ]
Step 4.3.12
Add 0 and 0.
p(λ)=determinant[1-λ32110-1-λ3800-2-λ40002-λ]
p(λ)=determinant[1-λ32110-1-λ3800-2-λ40002-λ]
p(λ)=determinant[1-λ32110-1-λ3800-2-λ40002-λ]
Step 5
Find the determinant.
Tap for more steps...
Step 5.1
Choose the row or column with the most 0 elements. If there are no 0 elements choose any row or column. Multiply every element in column 1 by its cofactor and add.
Tap for more steps...
Step 5.1.1
Consider the corresponding sign chart.
|+-+--+-++-+--+-+|
Step 5.1.2
The cofactor is the minor with the sign changed if the indices match a - position on the sign chart.
Step 5.1.3
The minor for a11 is the determinant with row 1 and column 1 deleted.
|-1-λ380-2-λ4002-λ|
Step 5.1.4
Multiply element a11 by its cofactor.
(1-λ)|-1-λ380-2-λ4002-λ|
Step 5.1.5
The minor for a21 is the determinant with row 2 and column 1 deleted.
|32110-2-λ4002-λ|
Step 5.1.6
Multiply element a21 by its cofactor.
0|32110-2-λ4002-λ|
Step 5.1.7
The minor for a31 is the determinant with row 3 and column 1 deleted.
|3211-1-λ38002-λ|
Step 5.1.8
Multiply element a31 by its cofactor.
0|3211-1-λ38002-λ|
Step 5.1.9
The minor for a41 is the determinant with row 4 and column 1 deleted.
|3211-1-λ380-2-λ4|
Step 5.1.10
Multiply element a41 by its cofactor.
0|3211-1-λ380-2-λ4|
Step 5.1.11
Add the terms together.
p(λ)=(1-λ)|-1-λ380-2-λ4002-λ|+0|32110-2-λ4002-λ|+0|3211-1-λ38002-λ|+0|3211-1-λ380-2-λ4|
p(λ)=(1-λ)|-1-λ380-2-λ4002-λ|+0|32110-2-λ4002-λ|+0|3211-1-λ38002-λ|+0|3211-1-λ380-2-λ4|
Step 5.2
Multiply 0 by |32110-2-λ4002-λ|.
p(λ)=(1-λ)|-1-λ380-2-λ4002-λ|+0+0|3211-1-λ38002-λ|+0|3211-1-λ380-2-λ4|
Step 5.3
Multiply 0 by |3211-1-λ38002-λ|.
p(λ)=(1-λ)|-1-λ380-2-λ4002-λ|+0+0+0|3211-1-λ380-2-λ4|
Step 5.4
Multiply 0 by |3211-1-λ380-2-λ4|.
p(λ)=(1-λ)|-1-λ380-2-λ4002-λ|+0+0+0
Step 5.5
Evaluate |-1-λ380-2-λ4002-λ|.
Tap for more steps...
Step 5.5.1
Choose the row or column with the most 0 elements. If there are no 0 elements choose any row or column. Multiply every element in column 1 by its cofactor and add.
Tap for more steps...
Step 5.5.1.1
Consider the corresponding sign chart.
|+-+-+-+-+|
Step 5.5.1.2
The cofactor is the minor with the sign changed if the indices match a - position on the sign chart.
Step 5.5.1.3
The minor for a11 is the determinant with row 1 and column 1 deleted.
|-2-λ402-λ|
Step 5.5.1.4
Multiply element a11 by its cofactor.
(-1-λ)|-2-λ402-λ|
Step 5.5.1.5
The minor for a21 is the determinant with row 2 and column 1 deleted.
|3802-λ|
Step 5.5.1.6
Multiply element a21 by its cofactor.
0|3802-λ|
Step 5.5.1.7
The minor for a31 is the determinant with row 3 and column 1 deleted.
|38-2-λ4|
Step 5.5.1.8
Multiply element a31 by its cofactor.
0|38-2-λ4|
Step 5.5.1.9
Add the terms together.
p(λ)=(1-λ)((-1-λ)|-2-λ402-λ|+0|3802-λ|+0|38-2-λ4|)+0+0+0
p(λ)=(1-λ)((-1-λ)|-2-λ402-λ|+0|3802-λ|+0|38-2-λ4|)+0+0+0
Step 5.5.2
Multiply 0 by |3802-λ|.
p(λ)=(1-λ)((-1-λ)|-2-λ402-λ|+0+0|38-2-λ4|)+0+0+0
Step 5.5.3
Multiply 0 by |38-2-λ4|.
p(λ)=(1-λ)((-1-λ)|-2-λ402-λ|+0+0)+0+0+0
Step 5.5.4
Evaluate |-2-λ402-λ|.
Tap for more steps...
Step 5.5.4.1
The determinant of a 2×2 matrix can be found using the formula |abcd|=ad-cb.
p(λ)=(1-λ)((-1-λ)((-2-λ)(2-λ)+04)+0+0)+0+0+0
Step 5.5.4.2
Simplify the determinant.
Tap for more steps...
Step 5.5.4.2.1
Simplify each term.
Tap for more steps...
Step 5.5.4.2.1.1
Expand (-2-λ)(2-λ) using the FOIL Method.
Tap for more steps...
Step 5.5.4.2.1.1.1
Apply the distributive property.
p(λ)=(1-λ)((-1-λ)(-2(2-λ)-λ(2-λ)+04)+0+0)+0+0+0
Step 5.5.4.2.1.1.2
Apply the distributive property.
p(λ)=(1-λ)((-1-λ)(-22-2(-λ)-λ(2-λ)+04)+0+0)+0+0+0
Step 5.5.4.2.1.1.3
Apply the distributive property.
p(λ)=(1-λ)((-1-λ)(-22-2(-λ)-λ2-λ(-λ)+04)+0+0)+0+0+0
p(λ)=(1-λ)((-1-λ)(-22-2(-λ)-λ2-λ(-λ)+04)+0+0)+0+0+0
Step 5.5.4.2.1.2
Simplify and combine like terms.
Tap for more steps...
Step 5.5.4.2.1.2.1
Simplify each term.
Tap for more steps...
Step 5.5.4.2.1.2.1.1
Multiply -2 by 2.
p(λ)=(1-λ)((-1-λ)(-4-2(-λ)-λ2-λ(-λ)+04)+0+0)+0+0+0
Step 5.5.4.2.1.2.1.2
Multiply -1 by -2.
p(λ)=(1-λ)((-1-λ)(-4+2λ-λ2-λ(-λ)+04)+0+0)+0+0+0
Step 5.5.4.2.1.2.1.3
Multiply 2 by -1.
p(λ)=(1-λ)((-1-λ)(-4+2λ-2λ-λ(-λ)+04)+0+0)+0+0+0
Step 5.5.4.2.1.2.1.4
Rewrite using the commutative property of multiplication.
p(λ)=(1-λ)((-1-λ)(-4+2λ-2λ-1-1λλ+04)+0+0)+0+0+0
Step 5.5.4.2.1.2.1.5
Multiply λ by λ by adding the exponents.
Tap for more steps...
Step 5.5.4.2.1.2.1.5.1
Move λ.
p(λ)=(1-λ)((-1-λ)(-4+2λ-2λ-1-1(λλ)+04)+0+0)+0+0+0
Step 5.5.4.2.1.2.1.5.2
Multiply λ by λ.
p(λ)=(1-λ)((-1-λ)(-4+2λ-2λ-1-1λ2+04)+0+0)+0+0+0
p(λ)=(1-λ)((-1-λ)(-4+2λ-2λ-1-1λ2+04)+0+0)+0+0+0
Step 5.5.4.2.1.2.1.6
Multiply -1 by -1.
p(λ)=(1-λ)((-1-λ)(-4+2λ-2λ+1λ2+04)+0+0)+0+0+0
Step 5.5.4.2.1.2.1.7
Multiply λ2 by 1.
p(λ)=(1-λ)((-1-λ)(-4+2λ-2λ+λ2+04)+0+0)+0+0+0
p(λ)=(1-λ)((-1-λ)(-4+2λ-2λ+λ2+04)+0+0)+0+0+0
Step 5.5.4.2.1.2.2
Subtract 2λ from 2λ.
p(λ)=(1-λ)((-1-λ)(-4+0+λ2+04)+0+0)+0+0+0
Step 5.5.4.2.1.2.3
Add -4 and 0.
p(λ)=(1-λ)((-1-λ)(-4+λ2+04)+0+0)+0+0+0
p(λ)=(1-λ)((-1-λ)(-4+λ2+04)+0+0)+0+0+0
Step 5.5.4.2.1.3
Multiply 0 by 4.
p(λ)=(1-λ)((-1-λ)(-4+λ2+0)+0+0)+0+0+0
p(λ)=(1-λ)((-1-λ)(-4+λ2+0)+0+0)+0+0+0
Step 5.5.4.2.2
Add -4+λ2 and 0.
p(λ)=(1-λ)((-1-λ)(-4+λ2)+0+0)+0+0+0
Step 5.5.4.2.3
Reorder -4 and λ2.
p(λ)=(1-λ)((-1-λ)(λ2-4)+0+0)+0+0+0
p(λ)=(1-λ)((-1-λ)(λ2-4)+0+0)+0+0+0
p(λ)=(1-λ)((-1-λ)(λ2-4)+0+0)+0+0+0
Step 5.5.5
Simplify the determinant.
Tap for more steps...
Step 5.5.5.1
Combine the opposite terms in (-1-λ)(λ2-4)+0+0.
Tap for more steps...
Step 5.5.5.1.1
Add (-1-λ)(λ2-4) and 0.
p(λ)=(1-λ)((-1-λ)(λ2-4)+0)+0+0+0
Step 5.5.5.1.2
Add (-1-λ)(λ2-4) and 0.
p(λ)=(1-λ)((-1-λ)(λ2-4))+0+0+0
p(λ)=(1-λ)((-1-λ)(λ2-4))+0+0+0
Step 5.5.5.2
Expand (-1-λ)(λ2-4) using the FOIL Method.
Tap for more steps...
Step 5.5.5.2.1
Apply the distributive property.
p(λ)=(1-λ)(-1(λ2-4)-λ(λ2-4))+0+0+0
Step 5.5.5.2.2
Apply the distributive property.
p(λ)=(1-λ)(-1λ2-1-4-λ(λ2-4))+0+0+0
Step 5.5.5.2.3
Apply the distributive property.
p(λ)=(1-λ)(-1λ2-1-4-λλ2-λ-4)+0+0+0
p(λ)=(1-λ)(-1λ2-1-4-λλ2-λ-4)+0+0+0
Step 5.5.5.3
Simplify each term.
Tap for more steps...
Step 5.5.5.3.1
Rewrite -1λ2 as -λ2.
p(λ)=(1-λ)(-λ2-1-4-λλ2-λ-4)+0+0+0
Step 5.5.5.3.2
Multiply -1 by -4.
p(λ)=(1-λ)(-λ2+4-λλ2-λ-4)+0+0+0
Step 5.5.5.3.3
Multiply λ by λ2 by adding the exponents.
Tap for more steps...
Step 5.5.5.3.3.1
Move λ2.
p(λ)=(1-λ)(-λ2+4-(λ2λ)-λ-4)+0+0+0
Step 5.5.5.3.3.2
Multiply λ2 by λ.
Tap for more steps...
Step 5.5.5.3.3.2.1
Raise λ to the power of 1.
p(λ)=(1-λ)(-λ2+4-(λ2λ1)-λ-4)+0+0+0
Step 5.5.5.3.3.2.2
Use the power rule aman=am+n to combine exponents.
p(λ)=(1-λ)(-λ2+4-λ2+1-λ-4)+0+0+0
p(λ)=(1-λ)(-λ2+4-λ2+1-λ-4)+0+0+0
Step 5.5.5.3.3.3
Add 2 and 1.
p(λ)=(1-λ)(-λ2+4-λ3-λ-4)+0+0+0
p(λ)=(1-λ)(-λ2+4-λ3-λ-4)+0+0+0
Step 5.5.5.3.4
Multiply -4 by -1.
p(λ)=(1-λ)(-λ2+4-λ3+4λ)+0+0+0
p(λ)=(1-λ)(-λ2+4-λ3+4λ)+0+0+0
Step 5.5.5.4
Move 4.
p(λ)=(1-λ)(-λ2-λ3+4λ+4)+0+0+0
Step 5.5.5.5
Reorder -λ2 and -λ3.
p(λ)=(1-λ)(-λ3-λ2+4λ+4)+0+0+0
p(λ)=(1-λ)(-λ3-λ2+4λ+4)+0+0+0
p(λ)=(1-λ)(-λ3-λ2+4λ+4)+0+0+0
Step 5.6
Simplify the determinant.
Tap for more steps...
Step 5.6.1
Combine the opposite terms in (1-λ)(-λ3-λ2+4λ+4)+0+0+0.
Tap for more steps...
Step 5.6.1.1
Add (1-λ)(-λ3-λ2+4λ+4) and 0.
p(λ)=(1-λ)(-λ3-λ2+4λ+4)+0+0
Step 5.6.1.2
Add (1-λ)(-λ3-λ2+4λ+4) and 0.
p(λ)=(1-λ)(-λ3-λ2+4λ+4)+0
Step 5.6.1.3
Add (1-λ)(-λ3-λ2+4λ+4) and 0.
p(λ)=(1-λ)(-λ3-λ2+4λ+4)
p(λ)=(1-λ)(-λ3-λ2+4λ+4)
Step 5.6.2
Expand (1-λ)(-λ3-λ2+4λ+4) by multiplying each term in the first expression by each term in the second expression.
p(λ)=1(-λ3)+1(-λ2)+1(4λ)+14-λ(-λ3)-λ(-λ2)-λ(4λ)-λ4
Step 5.6.3
Combine the opposite terms in 1(-λ3)+1(-λ2)+1(4λ)+14-λ(-λ3)-λ(-λ2)-λ(4λ)-λ4.
Tap for more steps...
Step 5.6.3.1
Reorder the factors in the terms 1(4λ) and -λ4.
p(λ)=1(-λ3)+1(-λ2)+14λ+14-λ(-λ3)-λ(-λ2)-λ(4λ)-14λ
Step 5.6.3.2
Subtract 4λ from 14λ.
p(λ)=1(-λ3)+1(-λ2)+14-λ(-λ3)-λ(-λ2)-λ(4λ)+0
Step 5.6.3.3
Add 1(-λ3)+1(-λ2)+14-λ(-λ3)-λ(-λ2)-λ(4λ) and 0.
p(λ)=1(-λ3)+1(-λ2)+14-λ(-λ3)-λ(-λ2)-λ(4λ)
p(λ)=1(-λ3)+1(-λ2)+14-λ(-λ3)-λ(-λ2)-λ(4λ)
Step 5.6.4
Simplify each term.
Tap for more steps...
Step 5.6.4.1
Multiply -λ3 by 1.
p(λ)=-λ3+1(-λ2)+14-λ(-λ3)-λ(-λ2)-λ(4λ)
Step 5.6.4.2
Multiply -λ2 by 1.
p(λ)=-λ3-λ2+14-λ(-λ3)-λ(-λ2)-λ(4λ)
Step 5.6.4.3
Multiply 4 by 1.
p(λ)=-λ3-λ2+4-λ(-λ3)-λ(-λ2)-λ(4λ)
Step 5.6.4.4
Rewrite using the commutative property of multiplication.
p(λ)=-λ3-λ2+4-1-1λλ3-λ(-λ2)-λ(4λ)
Step 5.6.4.5
Multiply λ by λ3 by adding the exponents.
Tap for more steps...
Step 5.6.4.5.1
Move λ3.
p(λ)=-λ3-λ2+4-1-1(λ3λ)-λ(-λ2)-λ(4λ)
Step 5.6.4.5.2
Multiply λ3 by λ.
Tap for more steps...
Step 5.6.4.5.2.1
Raise λ to the power of 1.
p(λ)=-λ3-λ2+4-1-1(λ3λ1)-λ(-λ2)-λ(4λ)
Step 5.6.4.5.2.2
Use the power rule aman=am+n to combine exponents.
p(λ)=-λ3-λ2+4-1-1λ3+1-λ(-λ2)-λ(4λ)
p(λ)=-λ3-λ2+4-1-1λ3+1-λ(-λ2)-λ(4λ)
Step 5.6.4.5.3
Add 3 and 1.
p(λ)=-λ3-λ2+4-1-1λ4-λ(-λ2)-λ(4λ)
p(λ)=-λ3-λ2+4-1-1λ4-λ(-λ2)-λ(4λ)
Step 5.6.4.6
Multiply -1 by -1.
p(λ)=-λ3-λ2+4+1λ4-λ(-λ2)-λ(4λ)
Step 5.6.4.7
Multiply λ4 by 1.
p(λ)=-λ3-λ2+4+λ4-λ(-λ2)-λ(4λ)
Step 5.6.4.8
Rewrite using the commutative property of multiplication.
p(λ)=-λ3-λ2+4+λ4-1-1λλ2-λ(4λ)
Step 5.6.4.9
Multiply λ by λ2 by adding the exponents.
Tap for more steps...
Step 5.6.4.9.1
Move λ2.
p(λ)=-λ3-λ2+4+λ4-1-1(λ2λ)-λ(4λ)
Step 5.6.4.9.2
Multiply λ2 by λ.
Tap for more steps...
Step 5.6.4.9.2.1
Raise λ to the power of 1.
p(λ)=-λ3-λ2+4+λ4-1-1(λ2λ1)-λ(4λ)
Step 5.6.4.9.2.2
Use the power rule aman=am+n to combine exponents.
p(λ)=-λ3-λ2+4+λ4-1-1λ2+1-λ(4λ)
p(λ)=-λ3-λ2+4+λ4-1-1λ2+1-λ(4λ)
Step 5.6.4.9.3
Add 2 and 1.
p(λ)=-λ3-λ2+4+λ4-1-1λ3-λ(4λ)
p(λ)=-λ3-λ2+4+λ4-1-1λ3-λ(4λ)
Step 5.6.4.10
Multiply -1 by -1.
p(λ)=-λ3-λ2+4+λ4+1λ3-λ(4λ)
Step 5.6.4.11
Multiply λ3 by 1.
p(λ)=-λ3-λ2+4+λ4+λ3-λ(4λ)
Step 5.6.4.12
Rewrite using the commutative property of multiplication.
p(λ)=-λ3-λ2+4+λ4+λ3-14λλ
Step 5.6.4.13
Multiply λ by λ by adding the exponents.
Tap for more steps...
Step 5.6.4.13.1
Move λ.
p(λ)=-λ3-λ2+4+λ4+λ3-14(λλ)
Step 5.6.4.13.2
Multiply λ by λ.
p(λ)=-λ3-λ2+4+λ4+λ3-14λ2
p(λ)=-λ3-λ2+4+λ4+λ3-14λ2
Step 5.6.4.14
Multiply -1 by 4.
p(λ)=-λ3-λ2+4+λ4+λ3-4λ2
p(λ)=-λ3-λ2+4+λ4+λ3-4λ2
Step 5.6.5
Combine the opposite terms in -λ3-λ2+4+λ4+λ3-4λ2.
Tap for more steps...
Step 5.6.5.1
Add -λ3 and λ3.
p(λ)=-λ2+4+λ4+0-4λ2
Step 5.6.5.2
Add -λ2+4+λ4 and 0.
p(λ)=-λ2+4+λ4-4λ2
p(λ)=-λ2+4+λ4-4λ2
Step 5.6.6
Subtract 4λ2 from -λ2.
p(λ)=-5λ2+4+λ4
Step 5.6.7
Move 4.
p(λ)=-5λ2+λ4+4
Step 5.6.8
Reorder -5λ2 and λ4.
p(λ)=λ4-5λ2+4
p(λ)=λ4-5λ2+4
p(λ)=λ4-5λ2+4
Step 6
Set the characteristic polynomial equal to 0 to find the eigenvalues λ.
λ4-5λ2+4=0
Step 7
Solve for λ.
Tap for more steps...
Step 7.1
Substitute u=λ2 into the equation. This will make the quadratic formula easy to use.
u2-5u+4=0
u=λ2
Step 7.2
Factor u2-5u+4 using the AC method.
Tap for more steps...
Step 7.2.1
Consider the form x2+bx+c. Find a pair of integers whose product is c and whose sum is b. In this case, whose product is 4 and whose sum is -5.
-4,-1
Step 7.2.2
Write the factored form using these integers.
(u-4)(u-1)=0
(u-4)(u-1)=0
Step 7.3
If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.
u-4=0
u-1=0
Step 7.4
Set u-4 equal to 0 and solve for u.
Tap for more steps...
Step 7.4.1
Set u-4 equal to 0.
u-4=0
Step 7.4.2
Add 4 to both sides of the equation.
u=4
u=4
Step 7.5
Set u-1 equal to 0 and solve for u.
Tap for more steps...
Step 7.5.1
Set u-1 equal to 0.
u-1=0
Step 7.5.2
Add 1 to both sides of the equation.
u=1
u=1
Step 7.6
The final solution is all the values that make (u-4)(u-1)=0 true.
u=4,1
Step 7.7
Substitute the real value of u=λ2 back into the solved equation.
λ2=4
(λ2)1=1
Step 7.8
Solve the first equation for λ.
λ2=4
Step 7.9
Solve the equation for λ.
Tap for more steps...
Step 7.9.1
Take the specified root of both sides of the equation to eliminate the exponent on the left side.
λ=±4
Step 7.9.2
Simplify ±4.
Tap for more steps...
Step 7.9.2.1
Rewrite 4 as 22.
λ=±22
Step 7.9.2.2
Pull terms out from under the radical, assuming positive real numbers.
λ=±2
λ=±2
Step 7.9.3
The complete solution is the result of both the positive and negative portions of the solution.
Tap for more steps...
Step 7.9.3.1
First, use the positive value of the ± to find the first solution.
λ=2
Step 7.9.3.2
Next, use the negative value of the ± to find the second solution.
λ=-2
Step 7.9.3.3
The complete solution is the result of both the positive and negative portions of the solution.
λ=2,-2
λ=2,-2
λ=2,-2
Step 7.10
Solve the second equation for λ.
(λ2)1=1
Step 7.11
Solve the equation for λ.
Tap for more steps...
Step 7.11.1
Remove parentheses.
λ2=1
Step 7.11.2
Take the specified root of both sides of the equation to eliminate the exponent on the left side.
λ=±1
Step 7.11.3
Any root of 1 is 1.
λ=±1
Step 7.11.4
The complete solution is the result of both the positive and negative portions of the solution.
Tap for more steps...
Step 7.11.4.1
First, use the positive value of the ± to find the first solution.
λ=1
Step 7.11.4.2
Next, use the negative value of the ± to find the second solution.
λ=-1
Step 7.11.4.3
The complete solution is the result of both the positive and negative portions of the solution.
λ=1,-1
λ=1,-1
λ=1,-1
Step 7.12
The solution to λ4-5λ2+4=0 is λ=2,-2,1,-1.
λ=2,-2,1,-1
λ=2,-2,1,-1
 [x2  12  π  xdx ]